High-mass cluster ions of ionic liquids in positive-ion and negative-ion DART-MS and their application for wide-range mass calibrations - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2014)
Eight ionic liquids (ILs) are subjected to both positive-ion and negative-ion direct analyses in real time (DART) Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry (MS). First, their ability to deliver evenly distributed cluster ion series covering a wide m/z range is explored. Then, one of the ILs exhibiting particularly useful cluster ion series in either ion polarity is applied for mass calibration. Using 1-butyl-3-methylimidazolium tricyanomethide delivers positive cluster ions suitable for mass calibration in the m/z 100-4,000 range and covers the m/z 100-2,000 range in negative-ion DART-MS. The corresponding mass reference lists are provided for either polarity. Furthermore, based on 1-butyl-3-methylimidazolium tricyanomethide, a high-mass record of m/z > 5,000 for positive-ion DART-MS is presented. The mass calibration procedure is finally validated by application to established standard compounds such as polydimethylsiloxanes, perfluorononanoic acid, and Ultramark 1621, a mixture of hexakis (fluoroalkoxy) phosphazenes. Further proof is presented by consistent exact mass differences between adjacent cluster ions.